The Right to Privacy of Workers under Workplace Surveillance in China - Mengxuan, Chen (Central European Academy Law Review, 2025)
Article 1032 of the Civil Code of the People’s Republic of China, which came into force on 1 January 2021, establishes the right of personality as a separate chapter, and defines privacy for the first time: “Privacy is the undisturbed private life of a natural person and his private space, private activities, and private information that he/she does not want to be known to others.”1 The Personal Information Protection Law of the People’s Republic of China (Hereinafter: PIPL), effective since 1 November 2021, requires personal information processors in China to take technical measures and necessary steps to secure personal information (Article 42), comply with laws/regulations and agreements (Article 43), and publish rules for personal information protection (Article 44). At present, China does not have any systematic law for the installation of regulatory surveillance systems. Article 26 of the PIPL only relates to the collection of personal information in public places, which mandates the installation of personal identification equipment in public places for public safety purposes, while requiring prominent logo reminders, and collected personal data may only be used for public security purposes, unless with individual consent.2 The Chinese Labour Code and the Labour Contract Law only deal with the protection of the property of workers in China, and there are no clear provisions for the protection of workers’ privacy. In labour law cases, the most common view of the courts is that the purpose of installing cameras in the workplace is to ensure the safety of a particular workplace, which is a normal exercise of the employer’s right to supervise. Recently there have been no legal provisions defining workers’ right to privacy in the workplace. This article aims 1. to analyse the views on privacy in China from the historical perspective, and 2. to analyse workers’ right to privacy under workplace surveillance in China through the legislation and a case study on Chinese jurisprudence.